Deconstructing the dominant narrative of Sophiatown: An Indian perspective of the 1950s - Leta, Lesiba T. (HTS teologiese studies, 2020)
The cosmopolitan nature of Sophiatown is often revered as an exemplary case study for strives towards social cohesion within diverse communities. Rearticulating this notion, scholars who have written extensively on the history of Sophiatown have increasingly used lexicon such as ‘diverse’, ‘multicultural’ and ‘multiracial’ amongst a plethora of words describing Sophiatown. However, the usage of such terminologies and the acceptance of Sophiatown as a multiracial society often lack credible emphasis on the racial composition of the suburb, even amongst its prestigious writers. The historiography of Sophiatown has been, for many years, a victim of binary thinking and a tendency to view South African history as a black versus white trajectory. In the case of Sophiatown, the trajectory has been largely focused on the machinery of the state in removing black people from Sophiatown and relocating them to Meadowlands. Even more so, the stamina of the apartheid government in forcefully destroying Sophiatown was seen as victory over black people and the continuation of separate development and group areas. Consequently, the history of the Indian, mixed race and white population (who formed the minority population of Sophiatown) has received little if no attention. Having realised the existing vacuum in the history of Sophiatown, the onus of this article is deliberately aimed towards robustly diversifying and deconstructing the literature of Sophiatown through the inclusion of Indian perspectives on the socio-economic environment of the freehold township (the history of mixed race and white people needs extensive research). To achieve this objective, the article predominantly comprises perspectives derived from oral interviews conducted with former residents of the Sophiatown community.Contribution: The research critically unpacks the memories, experiences and agencies of Indian people in moulding a freehold township (Sophiatown) through formations of relationships and community networks. Furthermore, the research reveals the importance of oral history as a method of articulating pivotal trajectories and memories that fill lacunas in local histories.